THE STAGES OF SOLVING ENGINEERING PROBLEMS FROM PHYSICS AND ITS EDUCATIONAL AND METHODOLOGICAL SUPPORT - Nosirov Nizomiddin Baratovich (American Journals Publishing, 2023)
This article analyzes the characteristics of the supply structure based on the comparison of the stages of solving physical and engineering problems in the preparation of engineers for professional activities. The tasks of the developed teaching-methodical support in the educational process are presented.
Keywords: competence, model, analysis, theoretical knowledge, independent work, individual, invariant, physics course, educational and methodological support, educational process.